Mapping Migration, Identity, and Space
XV, 364 p. 27 illus., 24 illus. in color.
Keywords: This interdisciplinary collection of essays focuses on the ways in which movements of people across natural, political, and cultural boundaries shape identities that are inexorably linked to the geographical space that individuals on the move cross, inhabit, and leave behind. As conflicts over identities and space continue to erupt on a regular basis, this book reads the relationship between migration, identity, and space from a fresh and innovative perspective. Tabea Linhard is Professor of Spanish, Comparative Literature, and International Studies at Washington University in St. Louis, USA. Timothy H. Parsons holds a joint appointment as Professor of African History in the History Department and the African and African American Studies Department at Washington University in St. Louis, USA.